Implementasi Distributed File Server pada Apache Web Server - Novita Belinda Wunarso; Andrias Rusli; Michelle Angelica; Arabella Margaret Salim (ULTIMA InfoSys, 2013)
In this research, a Distributed File Server (DFS) is developed to manage the need of a large storage space in the server, especially when the multimedia files are saved permanently in the web server. In the development, Apache Web Server is used with 1 computer as the main server, 2 computers as file servers, and 1 computer as the client who sends request. The result from the implementation of the DFS is the usage of main server’s storage space can be reduced by 99,77% from the full usage condition, causing an optimization in the web server. Another parameter is also being tested by the implementation of the DFS, which is the index.html page’s average access time. When only one server is being used, the average access time is 2,327 second. Whereas, when three servers are being used, the average access time is 5,577 second. Index Terms - Apache, distributed file server, web server optimization, average access time